TINJAUAN SIYASAH SYAR’IYYAH TERHADAP DAMPAK PENERAPAN OTONOMI DAERAH PADA SISTEM PEMERINTAHAN DESA - Mohamad Aswin (Qaumiyyah: Jurnal Hukum Tata Negara, 2022)
Islam itself provides space for ijtihad in the area of ​​siyasa or politics or the state as long as it is for the benefit and justice and welfare in general. The establishment of a new autonomous region can be a solution to increase welfare and equitable development in an area. So that the research questions in the formulation of the problem are how the impact of the application of regional autonomy on the government system in Petimbe Village and how siyasah syar'iyyah reviews the impact of implementing regional autonomy on the government system in Petimbe Village. The empirical legal method through a qualitative approach is the method of this research. So the results of the study explain that the implementation of regional autonomy in the village government system has a good impact on the ongoing development of the village. With more flexibility for the village in determining the main things that are the needs of the community, trust in the government will gradually arise which can also lead to empowering the community to participate actively in building a village that is more autonomous from day to day. Even though the positive impact that is so large, autonomy itself also opens up many opportunities for KKN actors which arise as a result of the freedom of the village and region in work and Islam does not have specific recommendations on how the government should run its government, but that does not mean that Islam does not regulate it. Islam is a complex religion that regulates all aspects of life, even though in reality Islam does not clearly regulate how the wheels of government should be run, Islam has provided the foundations for how to live in a state and society, while these foundations are in the form of deliberation, justice, equality and equality. monotheism, all of which must be based on the benefit of its people. Abstrak Islam sendiri memberikan ruang ijtihad dalam wilayah siyasah atau politik atau negara asalkan demi kemaslahatan dan keadilan serta kesejateraan secara umum. Pembentukan daerah otonomi baru bisa menjadi solusi peningkatan kesejahteraan dan pemerataan pembangunan di suatu daerah. Sehingga yang menjadi pertanyaan penelitian dalam rumusan masalah adalah bagaimana dampak penerapan otonomi daerah pada sistem pemerintahan di Desa Petimbe dan bagaiama tinjauan siyasah syar’iyyah terhadap dampak penerapan otonomi daerah pada sistem pemerintahan di Desa Petimbe. Adapun metode hukum empris melalui pendekatan kualitatif menjadi metode penelitian ini. Sehingga hasil penelitian menjelaskan bahwa penerapan otonomi daerah pada sistem pemerintahan desa berdampak baik bagi berlangsungnya pembangunan desa. Dengan lebih leluasanya desa dalam menentukan hal-hal pokok yang jadi kebutuhan masyarakatnya maka lambat laun akan timbul kepercayaan kepada pemerintah yang juga dapat menimbulkan pendayagunaan masyarakat untuk turut serta aktif dalam membangun desa yang lebih otonom dari hari ke hari. Meskipun dampak positif yang begitu besar otonomi sendiri juga banyak membuka peluang bagi pelaku-pelaku KKN yang mana timbul akibat keleluasaan desa maupun daerah dalam bekerja, dan Islam tidak ada anjuran spesifik tentang bagaimana seharusnya pemerintah menjalankan roda pemerintahnya namun bukan berarti Islam tak mengaturnya. Islam adalah agama kompleks yang mengatur keseluruhan sendi kehidupan, meskipun pada kenyataanya Islam tak mengatur secara jelas bagaimana seharusnya roda pemerintahan dijalankan namun agama Islam telah memberikan landasan-landasan tentang bagaimana hidup bernegara dan bermasyrakat, adapun landasan-landasan itu berupa musyawarah, keadilan, persamaan dan tauhid yang semunya harus berdasar pada kemaslahatan umatnya.